Faktor-Faktor Yang Mempengaruhi Keputusan Konsumen Dalam Pembelian Melalui Aplikasi Lazada - Steven Tombi Ra'pak Langi; Althon K. Pongtuluran; Astriwati Biringkanae (Jurnal of Management and Social Sciences, 2024)
The aim of this research is to find out whether lifestyle, trust and security influence purchasing decisions through the Lazada application among students at the UKI Toraja Faculty of Economics. The data collection procedure for this research was to distribute questionnaires to 100 students at the Uki Toraja Faculty of Economics. Quantitative analysis of data with simple regression tests. The research results show that partially and simultaneously, lifestyle, trust and security variables influence purchasing decisions on the Lazada application.